2022
DOI: 10.1038/s41598-022-18578-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of dual specificity phosphatases (DUSPs) in melanoma cellular plasticity and drug resistance

Abstract: Melanoma cells exhibit phenotypic plasticity that allows transition from a proliferative and differentiated phenotype to a more invasive and undifferentiated or transdifferentiated phenotype often associated with drug resistance. The mechanisms that control melanoma phenotype plasticity and its role in drug resistance are not fully understood. We previously demonstrated that emergence of MAPK inhibitor (MAPKi)-resistance phenotype is associated with decreased expression of stem cell proliferation genes and inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 46 publications
3
9
0
Order By: Relevance
“…[20][21][22] DUSP proteins have also been noted to play a role in cellular plasticity and melanoma drug resistance. 23 We find significant upregulation of several DUSP family genes (DUSP 1, 5, 7, 8, 10) upon initiation of treatment in the sensitive but not the resistant lineages, whereas DUSP4 expression is strongly suppressed in the resistant but not the sensitive lineages (Figure 6b/c, Supplementary Figure 7). These DUSP effects are not seen in comparisons of the untreated-early (T0) vs. untreated-late (TC) samples.…”
Section: Early Response To Treatment Differs In Sensitive and Resista...mentioning
confidence: 79%
See 1 more Smart Citation
“…[20][21][22] DUSP proteins have also been noted to play a role in cellular plasticity and melanoma drug resistance. 23 We find significant upregulation of several DUSP family genes (DUSP 1, 5, 7, 8, 10) upon initiation of treatment in the sensitive but not the resistant lineages, whereas DUSP4 expression is strongly suppressed in the resistant but not the sensitive lineages (Figure 6b/c, Supplementary Figure 7). These DUSP effects are not seen in comparisons of the untreated-early (T0) vs. untreated-late (TC) samples.…”
Section: Early Response To Treatment Differs In Sensitive and Resista...mentioning
confidence: 79%
“…Specifically, the dual specific phosphatase (DUSP) family represents a promising potential target for intervention. 23,23…”
Section: Discussionmentioning
confidence: 99%
“…BCI is a small-molecule that acts as a dual-inhibitor of DUSP1 and DUSP6, exerting anti-tumorigenic activity in a wide range of cancer models ( Figure 1A ) ( Kaltenmeier et al, 2017 ; Wu et al, 2018 ; James et al, 2019 ; Ramkissoon et al, 2019 ; Duan et al, 2021 ; Nair et al, 2021 ; Singh et al, 2022 ). In SH-SY5Y human neuroblastoma cells, BCI elicits a dose-dependent decrease in ERK activity and reduces the viability of these cells ( Mendell and MacLusky, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Singh et al. [21] focused on MAPK pathway inhibitors against different DUSPs in relation to their contribution to plasticity and resistance and found that the downregulation of DUSP1 specifically leads to plasticity in melanoma cells. DUSPs are negative regulators of the MAPK pathway and act in tandem to maintain cell proliferation and survival.…”
Section: Cell‐intrinsic Pathways Involved In Cancer Cell Plasticitymentioning
confidence: 99%
“…Loss of Dual specificity phosphate-4 (DUSP4), a negative regulator of the MAP kinase superfamily, leads to the development of a CSC-like phenotype in basal breast cancer, which confers plasticity to cells [20]. Singh et al [21] focused on MAPK pathway inhibitors against different DUSPs in relation to their contribution to plasticity and resistance and found that the downregulation of DUSP1 specifically leads to plasticity in melanoma cells. DUSPs are negative regulators of the MAPK pathway and act in tandem to maintain cell proliferation and survival.…”
Section: Cell-intrinsic Pathways Involved In Cancer Cell Plasticitymentioning
confidence: 99%